The Impact of Timing of Delayed Autologous Breast Reconstruction following Postmastectomy Radiation Therapy on Postoperative Morbidity - Mirza, Humza N.; Berlin, Nicholas L.; Sugg, Kristoffer B.; Chen, Jung-Shen; Chung, Kevin C.; Momoh, Adeyiza O. (Journal of Reconstructive Microsurgery, 2023)
Background The ideal time to perform reconstruction after the completion of postmastectomy radiation therapy (PMRT) in patients with locally advanced breast cancer is currently unknown. We evaluate the association between the timing of delayed autologous breast reconstruction following PMRT and postoperative complications.Methods Patients who underwent mastectomy, PMRT, and then delayed autologous breast reconstruction from 2009 to 2016 were identified from the Truven Health MarketScan Research Databases. Timing of reconstruction following PMRT was grouped 0–3, 3–6, 6–12, 12–24, and after 24 months. Multivariable models were used to assess associations between timing of reconstruction following PMRT and key measures of morbidity.Results A total of 1,039 patients met inclusion criteria. The rate of any complications for the analytic cohort was 39.4%, including 13.3% of patients who experienced wound complications and 11.3% of patients requiring additional flaps. Unadjusted rates of complications increased from 23.4% between 0 and 3 months to 49.4% between 3 and 6 months and decreased thereafter. Need for additional flaps was highest within 3 to 6 months (14.0%). Multivariate analysis revealed higher rates of any complications when reconstruction was performed between 3 and 6 months (odds ratio [OR]: 3.04, p < 0.001), 6 and 12 months (OR: 2.66, p < 0.001), or 12 and 24 months (OR: 2.13, p = 0.001) after PMRT. No difference in complications were noted in reconstructions performed after 24 months compared with those performed before 3 months (p > 0.05). However, rates of wound complications were least likely in reconstructions after 24 months (OR: 0.34, p = 0.035).Conclusion These findings suggest plastic surgeons may consider performing autologous breast reconstruction early for select patients, before 3 months following PMRT without increasing postoperative morbidity.
Keywords: breast reconstruction; radiation; autologous breast reconstruction; timing; morbidity